Improving quality of service for internet protocol television and voice over internet protocol over long-term evolution networks. (27th March 2019) - Samrah, Ahmed Shaban; Khalil, Abeer Twakol; Ibrahim, Hegazi M.
In this paper, we have assessed the impact of metrics which can be viewed as highly effective standards of the quality of service (QoS) over long-term evolution (LTE) networks. Additionally, we have proposed the impact of changing more reliable scheduling techniques on the performance based on the simulation of 36 real-time scenarios especially the usage of smart antennas. The re-enactment comes about fulfil: 1) higher signal to noise ratio (SNR) rates reached to 40 dB; 2) bring down estimations of bit error rate (BER); 3) acceptable delay values 20 ms for internet protocol television (IPTV) and 80 ms for voice over internet protocol (VOIP); 4) improved throughput ranges based on using smart antenna technique which realises 300 packets/sec and zero packets drops so it is very important criteria in our proposed system that we access all of those technologies over smart antenna with overall enhancements nears to 95%.